2019
DOI: 10.1051/0004-6361/201834130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of molecular structure on the infrared signatures of astronomically relevant PAHs

Abstract: Emission bands from polycyclic aromatic hydrocarbons (PAHs) dominate the mid-infrared spectra of a wide variety of astronomical sources, encompassing nearly all stages of stellar evolution. Despite their similarities, details in band positions and shapes have allowed a classification of PAH emission to be developed. It has been suggested that this classification is in turn associated with the degree of photoprocessing of PAHs. Over the past decade, a more complete picture of the PAH interstellar life-cycle has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 40 publications
(28 reference statements)
4
30
0
Order By: Relevance
“…IRMPD spectrum of Py + using FELIX and a Paul-type quadrupole ion trap (unpublished data). See Bouwman et al for experimental details 58. …”
mentioning
confidence: 99%
“…IRMPD spectrum of Py + using FELIX and a Paul-type quadrupole ion trap (unpublished data). See Bouwman et al for experimental details 58. …”
mentioning
confidence: 99%
“…IR spectroscopy: We performed mid-IR action spectroscopy on a series of PAH cations ranging from small species such as naphthalene up to sizes that are astronomically relevant, with the largest species being dicoronylene (C 48 H 20 ). The PAHs studied in our experiments were selected to span various symmetry groups and degrees of compactness to investigate the effect of these parameters on the appearance of their respective IR spectra (Bouwman et al (2019)). From these studies we concluded that the most compact PAHs with the highest symmetry have IR spectra that best resemble the observed mid-IR bands, while PAHs with lower symmetry exhibit modes at frequencies that do not correspond to the main IR emission bands.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Historically, this was one of the first hints of the spiral structure of galaxies. The dust itself can be best observed by studying atomic and molecular signatures in the spectra (Bouwman et al, 2019).…”
Section: Interstellar Medium Tracersmentioning
confidence: 99%